The Rise of Non-Tuberculosis Mycobacterial Lung Disease - Ratnatunga, Champa N.; Lutzky, Viviana P.; Kupz, Andreas; Doolan, Denise L.; Reid, David W.; Field, Matthew; Bell, Scott C.; Thomson, Rachel M.; Miles, John J. (Frontiers in Immunology, 2020)
The incidence and number of deaths from nontuberculous mycobacterial (NTM) disease have been steadily increasing globally. These lesser known ‘cousins’ of Mycobacterium tuberculosis (TB) were once thought to be harmless environmental saprophytics and only dangerous to individuals with defective lung structure or the immunosuppressed. However, NTM are now commonly infecting seemingly immune competent children and adults at increasing rates through pulmonary infection. This is of concern as the pathology of NTM is difficult to treat. Indeed, NTM have become extremely antibiotic resistant, and now have been found to be internationally dispersed through person-to-person contact. The reasons behind this increase are only beginning to be elucidated. Solutions to the NTM problem are needed given NTM disease is more common in the tropics. Importantly, 40% of the world’s population live in the tropics and due to climate change, the Tropic of Capricorn is expanding which will increase NTM infection zones. This review catalogues the global and economic disease burden, at risk populations, treatment options, host-bacterial interaction, immune dynamics, recent developments and research priorities for NTM disease.